A Comparison of Order-Disorder in Several Families of Cubic Oxides - Subramani, T.; Voskanyan, A.; Jayanthi, K.; Abramchuk, M.; Navrotsky, A. (Frontiers in Chemistry, 2021)
Order - disorder on both cation and oxygen sites is a hallmark of fluorite-derived structures, including pyrochlores. Ordering can occur on long and short range scales and can result in persistent metastable states. In other cubic oxide systems, different types of disorder are seen. The purpose of this paper is to review and compare the types and energetics of order - disorder phenomena in several families of cubic oxides having pyrochlore, weberite, defect fluorite, perovskite, rocksalt, and spinel structures. The goal is a better understanding of how structure, composition, and energetic parameters determine the feasibility of different competing ordering processes in these diverse systems.